2021
DOI: 10.1002/smll.202006005
|View full text |Cite
|
Sign up to set email alerts
|

Interfacing Carbon Dots for Charge‐Transfer Processes

Abstract: Carbon dots (CDs) are a booming material and the most recent incomer in the big family of carbon nanostructures. Specifically, CDs are nanosized fluorescent core‐shell nanoparticles with tunable absorption and emission spectra, with high solubility in aqueous media and common organic solvents. Herein, the origins and the development of these unique nanoscale structures are discussed, key synthetic routes are briefly described, and the utilization of CDs in light‐induced charge‐transfer schemes is mainly focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…1a ); thus, the afterglow durations are limited to seconds as well 25 – 36 . Notably, the photoinduced electron transfer properties of CDs have been studied previously, and they have demonstrated that CDs can be used as both electron donors and electron acceptors 37 39 . Given these findings, photoinduced CT and CS states might be obtained by properly designing CD-organic molecule blends, consequently producing LPL (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1a ); thus, the afterglow durations are limited to seconds as well 25 – 36 . Notably, the photoinduced electron transfer properties of CDs have been studied previously, and they have demonstrated that CDs can be used as both electron donors and electron acceptors 37 39 . Given these findings, photoinduced CT and CS states might be obtained by properly designing CD-organic molecule blends, consequently producing LPL (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38] Including good chemical stability, water solubility, higher specific surface area, higher fluorescence quantum yield (QY), electron mobility, low-cost sources. [39][40][41] The drug-carrying property of CDs is also better than quantum dots, 42 In particular, CDs have outstanding inherent photoluminescence properties. 43 Generally speaking, CDs emit bright fluorescence by themselves under light, and their optical stability is excellent.…”
Section: Introductionmentioning
confidence: 99%
“…19 CQDs are carbon-based zerodimensional nanoparticles with particle sizes less than 10 nm that are composed of dispersed spherical carbon particles. 20 Their nuclei are generally formed by sp 2 hybridization, and they have two kinds of structures: lattices and nonlattices. 21 In 2004, Professor Xiaoyou Xu of the University of South Carolina et al reported for the first time that during the electrophoretic purification of single-walled carbon nanotubes, CQDs that can emit bright fluorescence were found in the products, 22 thus introducing CQDs and opening the door for scientific researchers to further explore them.…”
Section: Introductionmentioning
confidence: 99%